Evaluation of Gastrointestinal Pathogens in Children with Inflammatory Bowel Disease Using Multiplex Polymerase Chain Reaction - Çağan Appak, Yeliz; Appak, Özgür; Aksoy, Betül; Emir, Büşra; Sayiner, Ayça Arzu; Baran, Maşallah (Journal of Pediatric Infectious Diseases, 2024)
Objective Impaired gastrointestinal (GI) mucosa and immunosuppressant therapies increase the risk of secondary infection in patients with inflammatory bowel disease (IBD). This study evaluated the detection of pathogens in children with IBD using a gastrointestinal panel (GP). This is the first study to compare this method with clinical data from pediatric IBD patients.Methods Children with newly diagnosed IBD or experiencing disease flares were included. Demographic data, clinical and laboratory findings, treatments, treatment durations, and disease activity were analyzed. Stool samples were assessed using multiplex real-time polymerase chain reaction with QIAstat-Dx GP®. Results were compared between groups.Results Thirty-five patients with IBD were included in the study. Routine stool analyses detected rotavirus in one patient and Blastocystis hominis in another, while no microorganisms were identified in stool cultures. GP detected pathogenic microorganisms in 40% of patients, with a higher prevalence among those experiencing IBD flares (71.4%). Detected pathogens included Enteropathogenic Escherichia coli, Campylobacter spp., Enteroaggregative Escherichia coli, Clostridium difficile, and sapovirus. No significant statistical differences were found between positive and negative GP cases in terms of new/previous diagnosis, disease duration, clinical and laboratory findings, disease activity, and immunosuppressive treatment.Conclusion In our study, pathogenic microorganisms that could not be detected by routine clinical tests in patients with IBD could be detected by the GP. Most positive cases occurred in previously diagnosed patients undergoing immunosuppressive therapy. Due to its high cost, GPs should be used selectively, and detected pathogens should be carefully evaluated for clinical relevance.
Keywords: inflammatory bowel disease; gastrointestinal panel; polymerase chain reaction